The TRGB–SBF Project. II. Resolving the Virgo Cluster with JWST - Gagandeep S. Anand; R. Brent Tully; Yotam Cohen; Edward J. Shaya; Dmitry I. Makarov; Lidia N. Makarova; Maksim I. Chazov; John P. Blakeslee; Michele Cantiello; Joseph B. Jensen; Ehsan Kourkchi; Gabriella Raimondo (The Astrophysical Journal)
The Virgo Cluster is the nearest substantial cluster of galaxies to the Milky Way and a cornerstone of the extragalactic distance scale. Here, we present JWST/NIRCam observations that simultaneously cover the cores and halos of 10 galaxies in and around the Virgo Cluster and are designed to perform simultaneous measurements of the tip of the red giant branch (TRGB) and surface brightness fluctuations (SBF). Seven of the targets are within the Virgo Cluster and where we are able to resolve some of the cluster’s substructure, while an additional three provide important constraints on Virgo infall. The seven galaxies within Virgo itself all have SBF measurements from the Advanced Camera for Surveys Virgo Cluster Survey (ACSVCS). After adjusting the ACSVCS measurements for the offset from our new JWST TRGB measurements, we determine a distance to the Virgo Cluster of d  = 16.17 ± 0.25 (stat) ± 0.47 (sys) Mpc. The work presented here is part of a larger program to develop a Population II distance scale through the TRGB and SBF that is completely independent of the prominent Cepheid + Type Ia supernova ladder. The TRGB distances to the galaxies presented here, when combined with future SBF measurements, will provide a crucial step forward for determining whether or not systematic errors can explain the well-known “Hubble tension” or if there is significant evidence for cracks in the ΛCDM model.